Masses of vector and pseudovector hybrid mesons in a chiral symmetric model - Walaa I. Eshraim (SciPost Physics Proceedings, 2022)
We enlarge the chiral model, the so-called extended Linear Sigma Model (eLSM), by including the low-lying hybrid nonet with exotic quantum numbers $J^{PC}=1^{-+}$ and the nonet of their chiral partners with $J^{PC}=1^{+-}$ to a global $U(3)_r × U(3)_l$ chiral symmetry. We use the assignment of the $π_1^{hyb}= π_1(1600)$ as input to determine the unknown parameters. Then, we compute the lightest vector and pseudovector hybrid masses that could guide ongoing and upcoming experiments in searching for hybrids.